One-step synthesis of Pt/a-CoOx core/shell nanocomposites - Daewoon Kim (Applied Microscopy, 2019)
Abstract Herein, we synthesize a core/shell Pt/a-CoOx nanocomposite via one-step synthesis using a strong reaction agent of borane t-butylamine(BBA) at 200 °C. Transmission electron microscopy study shows that the morphology of nanocomposites is controlled by the stirring time and perfect core/shell structure is formed with over 7 days stirring time.